A joint kinetic analysis of rugby place kicking technique to understand why kickers achieve different performance outcomes. (18th April 2019) - Atack, Alexandra C.; Trewartha, Grant; Bezodis, Neil E.
Abstract: We aimed to identify differences in kicking leg and torso mechanics between groups of rugby place kickers who achieve different performance outcomes, and to understand why these features are associated with varying levels of success. Thirty-three experienced place kickers performed maximum effort place kicks, whilst three-dimensional kinematic (240 Hz) and ground reaction force (960 Hz) data were recorded. Kicking leg and torso mechanics were compared between the more successful ('long') kickers and two sub groups of less successful kickers ('short' and 'wide-left') using magnitude-based inferences and statistical parametric mapping. Short kickers achieved substantially slower ball velocities compared with the long kickers (20.8 ± 2.2 m/s vs. 27.6 ± 1.7 m/s, respectively) due to performing substantially less positive hip flexor (normalised mean values = 0.071 vs. 0.092) and knee extensor (0.004 vs. 0.009) joint work throughout the downswing, which may be associated with their more front-on body orientation, and potentially a lack of strength or intent. Wide-left kickers achieved comparable ball velocities (26.9 ± 1.6 m/s) to the long kickers, but they were less accurate due to substantially more longitudinal ball spin and a misdirected linear ball velocity. Wide-left kickers created a tension arc across the torso and therefore greater positive hip flexor joint work (normalised mean = 0.112) throughout the downswing than the long kickers. Whilst this may have assisted kicking foot velocity, it also induced greater longitudinal torso rotation during the downswing, and may have affected the ability of the hip to control the direction of the foot trajectory.